1999
DOI: 10.1021/jf990608v
|View full text |Cite
|
Sign up to set email alerts
|

Novel Trisaccharide Fatty Acid Ester Identified from the Fruits of Morinda citrifolia (Noni)

Abstract: Two known glycosides and a novel trisaccharide fatty acid ester were isolated from the n-butanol-soluble fraction of the fruits of Morinda citrifolia (noni). Structure determination was carried out by spectral techniques such as MS, IR, NMR, and 2D-NMR. The novel trisaccharide fatty acid ester was elucidated as 2, 6-di-O-(beta-D-glucopyranosyl)-1-O-octanoyl-beta-D-glucopyranose. The known compounds were identified as rutin and asperulosidic acid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
61
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(67 citation statements)
references
References 10 publications
5
61
0
1
Order By: Relevance
“…Further studies on Noni-ppt suggested that it suppress the tumor growth through release of TNF-, IL-1ß, IL-10, IL-12 p70, IFN-, and nitric oxide (Hirazumi & Furusawa, 1999). Some individual compounds from Noni juice were reported to function as ras inhibitors and thus suppressed the rasexpressing tumors (Wang et al, 1999). Liu et al (2001) found that the antitumor potential of noni fruit due to the presence of glycosides and asperulosidic acid extracted from the noni fruit on the AP-1 transactivation and cell transformation in mouse epidermal JB6 cells.…”
Section: Anticancer Activitymentioning
confidence: 99%
“…Further studies on Noni-ppt suggested that it suppress the tumor growth through release of TNF-, IL-1ß, IL-10, IL-12 p70, IFN-, and nitric oxide (Hirazumi & Furusawa, 1999). Some individual compounds from Noni juice were reported to function as ras inhibitors and thus suppressed the rasexpressing tumors (Wang et al, 1999). Liu et al (2001) found that the antitumor potential of noni fruit due to the presence of glycosides and asperulosidic acid extracted from the noni fruit on the AP-1 transactivation and cell transformation in mouse epidermal JB6 cells.…”
Section: Anticancer Activitymentioning
confidence: 99%
“…In another processing method, the mature fruit (light amber colour) is pressed and the resulting juice becomes the finished product (RUSSELL, 2000). Although the noni fruits have been used as a food, very few reports on their chemical composition are available (WANG, 1999;ROSS, 2001;KAMIYA, 2004;CHAN-BLANCO et al, 2006;POTTERAT;HAMBURGER, 2007), all of them related with the non-volatile components. In this study, 51 volatile compounds of the ripe fruit were isolated and quantified by solvent extraction (FARINE et al, 1996), and 24 volatile constituents were identified by HS-SPME-GC-MS using a PDMS fiber from commercial juices (LACHENMEIER et al, 2006).…”
mentioning
confidence: 99%
“…The Ca/Cb data of arylglycerol b-guaiacyl ether appeared at 72.1/84.4 (C-7ЉЉ/C-8ЉЉ) was indicative of erythro form. 22) The known phenolic compounds were classified to two phenolic glycosides (3,4,5-trimethoxyphenyl-b-D-glucopyranoside 23) and 1-[a-L-rhamnopyranosyl-(1→6)-b-D-glucopyranosyloxy]-3,4,5-trimethoxybenzene, 24) ) four flavonoids (tricin, rutin, 25) nicotiflorin, and myricetin-3-O-rutinoside 26) ), and six lignans (lyoniside, 27) 29) and hedyotisols A-C 21) ), and their structures were identified by comparison of spectroscopic data with those in literature. All of the known compounds were isolated from mangrove plants for the first time.…”
mentioning
confidence: 99%